The Influence of Gender, Type of Sport, and Social Support on the Formation of Positive Values among Adolescents - Shofie Vega; Amung Ma'mun; Sucipto (Universitas Negeri Semarang, 2026)
Sports are widely recognized as an important medium for cultivating positive values in adolescents. This study aims to analysis the impact of gender, sport type, and social support on the development of positive values in adolescents using the Systematic Literature Review (SLR) method. The review was conducted on 8 selected articles from 738 documents collected following the PRISMA guidelines and inclusion-exclusion criteria. The results showed that the type of sport (individual or team) influences the formation of different values, including responsibility, cooperation, and leadership. Gender factors play a role in shaping adolescents' experiences and social roles in the sport context, while social support from parents, peers, and teachers strengthens motivation and character development. The conclusion is that the formation of positive values in adolescents through sport is the result of the interaction of various factors, namely individual factors, sport type, and social support. Therefore, an integrative and contextual approach with the Positive Youth Development (PYD) framework is needed. This study provides a basis for developing education and sports policies that support the development of positive character comprehensively.